CTD/LADCP-data in the western part of the Romanche Fracture Zone in 2011-2014 - Roman Y Tarakanov; Eugene G Morozov (PANGAEA, 2018)
The data set contains the processed CTD / LADCP data of 25 hydrographic stations performed in the western part of the equatorial Romanche Fracture Zone in 2011-2014 from the R/V "Akademik Sergey Vavilov". The processing of the raw data was carried out by standard processing packages SBE Data Processing and the LADCP Processing, version IX.8. The temperature and salinity data are given with an interval of 2 db. The LADCP data are given with an interval of 8 or 16 m. The files of the LADCP processing protocols and the figures generated by processing package are given.
Supplement to: Tarakanov, Roman Y; Morozov, Eugene G; van Haren, Hans; Makarenko, Nikolay; Demidova, Tatiana A (2018): Structure of the Deep Spillway in the Western Part of the Romanche Fracture Zone. Journal of Geophysical Research: Oceans, 123(11), 8508-8531, https://doi.org/10.1029/2018JC013961